Challenge and threat motivation : Effects on superficial and elaborative information processing - Fonseca, Ricardo Jorge Rodrigues Moita da (2014)
This paper integrates the motivational states of challenge and threat within a dual processing perspective. Previous research has demonstrated that individuals experience a challenge state when individuals have sufficient resources to cope with the demands of a task (Blascovich eta, 1993). Because the experience of resource availability has been shown to be associated with superficial processing (Garcia-Marques and Mackie, 2007), we tested the hypothesis that challenge is associated with superficial processing in two persuasion experiments. Experiment 1 revealed that inducing attitudes of participants in a challenge state was not sensitive to the quality of arguments presented. Experiment 2 demonstrated that the effect occurs even when task engagement, manipulated by the presence (vs. the absence) of a task observer (Blascovich et al., 1993), is high. The implications of these results for the biopsychosocial model model and the cognitive and motivational literature are discussed.